The Influence of Interactive Animation Media on Students' Interest in Learning in View of Learning Results in Class IV Science Subjects at SD Inpres Kuanino 3 - Adu, Rivaldo; Benu, Asti Yunita; Naitili, Cornelia Amanda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The use of visual and auditory elements into the learning process may enhance its effectiveness, captivate students, and facilitate their comprehension and engagement with the topic. Educators have the power to enhance classroom instruction by doing things like creating a sense of intrinsic motivation and offering post-lesson assessments. The objective of this research was to find out whether fourth graders at SD Inpres Kuanino 3 were more engaged in studying IPAS when they used animated interactive media. The experimental quay approach is used in this quantitative investigation. A total of 49 participants were included in the study, and the sampling method utilised was nonprobability saturation sampling. Data collecting approaches involving observation, testing and documentation. The data was examined by means of a t-test and hypothesis testing. Using a t-test, the researchers found that there was a 17.59 point difference between the experimental and control groups' average post-test scores: 82.59> 65.00. In addition, the sig value is revealed by the Independent Sample T-Test, which tests hypotheses. H0 is rejected while Ha is accepted when the two-sided p-value is less than 0.05. Students in SD Inpres Kuanino 3's fourth grade were shown to be much more engaged in learning when animated interactive media were used.